Osmium isotope stratigraphy of a marine ferromanganese crust - Klemm, V; Levasseur, S; Frank, M; Hein, JR; Halliday, A (2005)
Ferromanganese crusts provide records of long term change in ocean circulation and continental weathering. However, calibrating their age prior to 10 Ma has been entirely based on empirical growth rate models using Co concentrations, which have inherently large uncertainties and fail to detect hiatuses and erosional events. We present a new method for dating these crusts by measuring their osmium (Os) isotope record and matching it to the well-known marine Os isotope evolution of the past 80 Ma. The well-characterised crust CD29-2 from the central Pacific, was believed to define a record of paleooceanographic change from 50 Ma. Previous growth rate estimates based on the Co method are consistent with the new Os isotope stratigraphy but the dating was grossly inaccurate due to long hiatuses that are now detectable. The new chronology shows that it in fact started growing prior to 70 Ma in the late Cretaceous and stopped growing or was eroded between 13.5 and 47 Ma. With this new technique it is now possible to exploit the full potential of the oceanographic and climatic records stored in Fe-Mn crusts. © 2005 Elsevier B.V. All rights reserved.